2011
DOI: 10.1113/jphysiol.2010.202614
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic control of micturition within the periaqueductal grey matter of the male rat

Abstract: Non-technical summary Even when the bladder is full, emptying can be deferred voluntarily until individuals find themselves in a socially appropriate environment. This indicates that the brain is important in the control of bladder function. This study used drugs that either mimic or block the effects of the neurotransmitter chemicals involved in communication between nerve cells to investigate the brain nerve circuits that govern the control of the bladder. A small region in the midbrain was shown to be criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 60 publications
(114 reference statements)
3
61
2
Order By: Relevance
“…Any central GABAergic pathways that are involved would have also been antagonized after administration of intravenous picrotoxin. Intrathecal blockade of GABA was important because central GABAergic mechanisms are known to exist in the PAG (42), and these results demonstrated that the GABAergic neurons participating in pudendal afferent stimulation-evoked inhibition are located in the lumbosacral spinal cord.…”
Section: Gabaergic Mechanisms Are Necessary For Bladder Inhibition Bymentioning
confidence: 95%
“…Any central GABAergic pathways that are involved would have also been antagonized after administration of intravenous picrotoxin. Intrathecal blockade of GABA was important because central GABAergic mechanisms are known to exist in the PAG (42), and these results demonstrated that the GABAergic neurons participating in pudendal afferent stimulation-evoked inhibition are located in the lumbosacral spinal cord.…”
Section: Gabaergic Mechanisms Are Necessary For Bladder Inhibition Bymentioning
confidence: 95%
“…The authors concluded that the PAG does not have an essential role in reflex micturition but rather is involved in transmitting bladder filling information to higher brain centers. Subsequently, the techniques used in transection experiments were questioned by other investigators (593) who noted that the PAG lesions in the experiments of Tasaki et al (619) were often incomplete and a part of the caudal ventrolateral PAG was preserved in some experiments.…”
Section: Brain Stem Circuitry: Spinobulbospinal Micturition Reflexmentioning
confidence: 99%
“…Conversely excitatory neurons in the PAG that relay bladder afferent information to PMC direct neurons are likely to be "phasic micturition neurons" identified by Sakakibara et al (536). It is known that a GABAergic inhibitory mechanism in the PAG tonically controls the bladder volume set-point for initiating micturition (593). In the hypothetical circuit in Figure 22, this mechanism is represented by an independent inhibitory neuron synapsing with the PAG relay neuron.…”
Section: Computer Model Of Micturition Switching Circuitmentioning
confidence: 99%
See 2 more Smart Citations